Comparion of two techniques crosslinking for progressive keratectasia - L. N. Boriskina; I. A. Remesnikov; E. S. Blinkova; E. G. Solodkova (Oftalʹmologiâ, 2014)
Purpose: to compare surgical approaches, features of the postoperative period and functional results of conventional and opti- mized crosslinking techniques.Methods: We followed 2 groups of patients (10 patients, 10 eyes each), treated in Volgograd branch of the S.N. Fyodorov Eye Microsurgery Clinic for kerotoconus of the II-III degree according to the conventional method (I group) and the optimized technique (II group). the optimized technique consisted of the customized excimer laser corneal deepitalization to the depth of 2/3 of the epithelial layer. Excimer laser ablation with intraoperative «on-line» pachymetry was made by means of Schwind Amaris-500 Hz (Schwind, Germany).Results: Method of the optimized crosslinking with a customized depth of excimer laser ablation required a longer period for satu- ration of the cornea with solution of riboflavin (mean 5-10 minutes). However, it was accompanied with a less severe corneal syndrome, a complete reepithelization and an earlier postoperative recovery of visual functions. Six months postoperatively a 1-2-line improve- ment of BCVA and UCVA was achieved in 19 patients (19 eyes). Decrease of cylindrical component averaged 1.2 D in the group I and 1 D in the group II. Mean refraction change in SE was 2.2 D in the group I and 2.0 D in the group II. Six months postoperatively one patient from the group II had a 1-line regression of BCVA in comparison to the preoperative level accompanied with a 10 μm corneal thinning and corneal curvature steepening by 2 D at the top of keratoconus, which was regarded as an aggravation of initial state.Conclusion: Both approaches have proved their safety and effectiveness. However, incurrence of the above-mentioned case of state deterioration calls for the further comparative studies in order to evaluate clinical effectiveness of these methods.